[PP.17.10] STRAIN-DEPENDENT CARDIOVASCULAR AND RENAL CONSEQUENCES OF 5/6 NEPHRECTOMY IN 129/SV AND C57BL/6 MICE. (September 2017) - Guerrot, D.; Hamzaoui, M.; Bellien, J.
Abstract : Objective: difficulty to create reproducible experimental models of cardiovascular diseases in mice is highly linked to differences between strains. 5/6 nephrectomy (5/6 Nx) is the most frequently used model to induce chronic kidney disease (CKD) in rodents. In the absence of comparative analysis in the literature, we evaluated the cardiovascular and renal consequences of 5/6 Nx in 129/Sv and C57Bl/6 mice. Design and method: 5/6 Nx was induced in 8 weeks-old 129/Sv and C57BL/6J male mice, by performing 2/3 left nephrectomy, and a right nephrectomy one week later. Plasma creatinine was mesured 10 weeks after 5/6 Nx. Arterial blood pressure was monitored by plethysmography 4 and 8 weeks after 5/6 Nx. Heart function was monitored by echocardiography before sacrifice. Histological analyses of the remnant kidney were performed after sacrifice. Results: 10 weeks following 5/6 Nx, CKD was demonstrated by a significant increase in plasma creatinine in both 129/Sv (+26 μmol/l vs sham) and C57Bl/6 mice (+15 μmol/l). Polyuria and kidney histological lesions were more pronounced in 129/Sv than in C57Bl/6 mice. Increase in albuminuria was significant in 129/Sv (+1558 μg/24 h), but not in C57Bl/6 mice (+26.1 μg/24 h). Similarly, the increase in SBP was significant only in 129/Sv mice (+20 mmHg; +8.4 mmHg in C57Bl/6). Echocardiography revealed significant alterations in systolic (LVEF -11%) and diastolic function (E/A -0.32) in the 129/Sv genetic background, but these modifications were not signficant in C57Bl/6 mice. Heart weight increased significantly in 129/Sv mice after 5/6 Nx (+40.1 mg) but not in C57Bl6/J mice. Conclusions: Kidney and cardiovascular damage after standardized 5/6 Nx was more pronounced in 129/Sv than in C57BL/6 mice. This study suggests that the use of this model in 129/Sv mice is relevant to study the cardiovascular consequences of CKD, while an increased severity of the experimental model may be required in C57Bl/6 mice.